Effect of unsteady relative thermal and concentration boundary layer thickness on mixed convection in a partially heated contaminated enclosure - C.N. Mithun; Md.Jahid Hasan; A.K. Azad; Rumman Hossain; M.M. Rahman (South African Journal of Chemical Engineering, 2022)
Double diffusive flow under mixed convection has become a significant area of research. This study aims to evaluate the Lewis number effect in such a double-diffusive problem in a roof-based air-ventilated system. The Lewis number 0.01 ≤ Le ≤ 5 was chosen for the study, considering other parameters as constant to observe the impact of different heat and mass transfer properties varying the dimensionless time 0.1 ≤ τ ≤ 1. The Galerkin residual technique was chosen to generate the governing equations. The outcomes have been plotted in streamlines, isotherms, isoconcentration, heat and mass transfer, average fluid temperature and mass concentration. The major findings elucidate that heat and mass transfer rate augments when Lewis number goes higher and vice versa. Moreover, when the thermal diffusivity is higher than the mass diffusivity, the average fluid temperature and mass concentration become lower. Overall, this study will be a guide on double-diffusive system design, such as roof-based air ventilation systems.